Proceso de selección del talento humano en el GAD (Gobierno Autónomo Descentralizado) Parroquial Antonio Sotomayor del Cantón Vinces. - Leon Gurumendi, Narexi Lorena (2018)
The Autonomous Decentralized Government (GAD) Parochial Antonio Sotomayor del Canton Vinces, is a sectional government institution that administers the parish in a way autonomous, through public, political, administrative and financial management. The Boards parishes enjoy conscious administrative autonomy in the full exercise of the faculty organization and management of their human talents and material resources, for the fulfillment of their responsibilities and competences